(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Translating dance into words may seem unlikely, but it is precisely through an analogous arrangement that individuals with visual impairments can appreciate performances in this field. Audio description is a cultural accessibility resource that provides this access through an intersemiotic translation process, enabling the transformation of visual language into verbal language. Based on this understanding, we reflect on how audio description and dramaturgy can walk hand in hand in dance creation processes, so that what is translated from dance does not become a mere descriptive text of what is seen, but above all, of what dance delineates and awakens in the ephemerality of performances. To this end, some extracts from shows at the Festival Acessibilidança Virtual, organised by FUNARTE in 2022, are used as references. Therefore, we are concerned with concentrating efforts in order to identify what developments will be necessary so that an audio description of dance, aligned with dramaturgy, to preserve the poetics of the artistic work and also be engaging for the visually impaired audience.